KELAYAKAN SARANA DAN PRASARANA BENGKEL TEKNIK SEPEDA MOTOR DI SMK NASIONAL BERBAH - Ananda Eko Wahyudi; Slamet Priyanto; Alfath Khaharsyah (JURNAL VOKASI DEWANTARA (JVD), 2025)
The Feasibility of Facilities and Infrastructure for Motorcycle Engineering Workshop at Berbah National Vocational School. Thesis. Mechanical Engineering Vocational Education Study Program, Faculty of Teacher Training and Education, Tamansiswa Bachelorwiayata University, Yogyakarta. 2023. This study aims to determine: (1) The level of feasibility of motorcycle engineering workshop facilities at Berbah National Vocational School. (2) The feasibility level of the motorcycle engineering workshop infrastructure at Berbah National Vocational School. This research is a qualitative descriptive study. The subjects in this study were the head of the workshop and teaching teachers in the motorcycle engineering workshops. The object of research is the facilities and infrastructure of motorcycle engineering workshops. Data collection techniques in this study were observation, interviews and documentation. Deskritive statistics are used in the analysis of thisresearch data and the calculation process uses a percentage scale. The results of this study indicate that: (1) The feasibility level of the facilities from the four work areas is included in the less feasible category with an average eligibility percentage value of 25.90%. Review of research result is carried out based on predetermined standards, for furnitur and equipment in each work area. (2) The feasibility level of the motorbike practice workshop infrastructure at SMK Nasional Berbah can be categorized as inadequate, in terms of the motorcycle engine repair work area of 0.77 m2/student, the body and electricity work area of 0.58 m2/student, storage space for motorcycle components 0.58 m2/student, and storage space for instructors and 0.48 m2/student.